Stuart Hall and the tension between academic and intellectual work. (January 2016) - Ang, Ien
Throughout his long career Stuart Hall has personified a shifting range of political-intellectual positionalities, responding to the changing historical conjuncture in the West since the late 1950s. From his engagement with the New Left to the generation of new spaces for critical intellectual intervention in the 1970s (as embodied by the Birmingham Centre for Contemporary Cultural Studies) to the tightening up of such spaces as a consequence of the neoliberal ascendancy (which Hall himself theorized through his analysis of Thatcherism) from the 1980s onwards, the role of the intellectual/academic has changed significantly throughout this period, as universities have become increasingly corporatized. This article tracks this evolution by tracing the paradoxical fate of cultural studies as an intellectual project and academic formation, and Hall's ultimate distancing from it at the end of his life.